2019
DOI: 10.1161/jaha.118.011824
|View full text |Cite
|
Sign up to set email alerts
|

Role of Perivascular Oligodendrocyte Precursor Cells in Angiogenesis After Brain Ischemia

Abstract: Background Oligodendrocyte precursor cells ( OPC s) regulate neuronal, glial, and vascular systems in diverse ways and display phenotypic heterogeneity beyond their established role as a reservoir for mature oligodendrocytes. However, the detailed phenotypic changes of OPC s after cerebral ischemia remain largely unknown. Here, we aimed to investigate the roles of reactive OPC s in the ischemic brain. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
4
31
1
Order By: Relevance
“…Oligodendrocyte precursor cells (OPCs) have recently emerged as one of the contributors to BBB. According to their regional differences, OPCs can be divided into two subtypes, namely, perivascular OPCs and parenchymal OPCs (Maki, 2017;Kishida et al, 2019). In the human and mouse brain, perivascular OPCs are attached to cerebral endothelial cells and pericytes through basal lamina, and thereby are thought to become novel components of the BBB (Seo et al, 2013;Maki et al, 2015).…”
Section: Oligodendrocyte Precursor Cells and Pericytesmentioning
confidence: 99%
“…Oligodendrocyte precursor cells (OPCs) have recently emerged as one of the contributors to BBB. According to their regional differences, OPCs can be divided into two subtypes, namely, perivascular OPCs and parenchymal OPCs (Maki, 2017;Kishida et al, 2019). In the human and mouse brain, perivascular OPCs are attached to cerebral endothelial cells and pericytes through basal lamina, and thereby are thought to become novel components of the BBB (Seo et al, 2013;Maki et al, 2015).…”
Section: Oligodendrocyte Precursor Cells and Pericytesmentioning
confidence: 99%
“…This oligodendrogenesis has been shown to improve brain repair processes and neurological scores (Zhang et al, 2013). After brain ischemia, OPCs also seem to be involved in post-stroke angiogenesis (Kishida et al, 2019), a process linked to neurogenesis (Xiong et al, 2010). Indeed, OPCs in the cerebral cortex shift from a parenchymal to a perivascular subtype.…”
Section: Oligodendrocyte/oligodendrocyte Progenitor Cell Recruitment mentioning
confidence: 99%
“…Examples are metachromatic leukodystrophies, Canavan disease or X-linked adrenoleukodystrophy. Beyond this, the de- and regeneration of oligodendrocytes appears to be an important pathological aspect of many other neuronal disorders including spinal cord injury, where remyelination improves functional recovery [ 33 ], Alzheimer’s disease, where myelination-related processes are recurrently perturbed in multiple cell types, suggesting that myelination has a key role in Alzheimer’s disease pathophysiology [ 34 ], or stroke, where it is believed that oligodendrocyte progenitor cells can promote angiogenesis [ 35 ]. Beyond this, it has recently been suggested that cells of the oligodendrocyte lineage can transform, under specific conditions, into antigen-presenting cells, suggesting that oligodendrocytes can act as active immunomodulators [ 36 ].…”
Section: Introductionmentioning
confidence: 99%